Food Contamination Survey: Content of Arsenic (As) in rice from supermarkets in North Africa and the Middle East. - F. Lawgali, Youssef; A. Meharg, Andy (Libyan Journal of Science &Technology, 2022)
The results of a market basket investigation conducted to determine the total levels of Arsenic (As) in rice purchased from supermarkets in North Africa and the Middle East (NA & MIDEA). Two hundred eighty samples of rice were collected from numerous large food supermarkets in towns and cities in NA and MIDEA: Morocco (MR), Libya (LB), Algeria (AL), Tunisia (TN), Egypt (EG), Jordan (JO) and Syria (SY). The average level of As in rice from NA & MIDEA is 0.22 mg/kg, comparable with average levels in Australia, although not representative of the levels in rice from the USA. The differences in As levels in rice from the nine countries of origin were found to be significant. The rice with the lowest grain As concentration, 0.05 mg/kg, was a short grain variety from Egypt, while the highest, 0.22 mg/kg, was found in a long grain rice from Australia.